1974
DOI: 10.1192/bjp.124.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of 53 Bipolar Manic-Depressive Patients

Abstract: Despite the monumental follow-up studies of patients with manic-depressive illness by Lund quist (i@@), Rennie (1942), Hastings (1958), and more recently, Shobe (1971), the develop ment of the concept of unipolar and bipolar forms of affective disorders with clinical (Brodie and Leff, 1971), genetic (Dunner et a!., ‘¿ 970; Winokur ci al., 1969), and biologic differences (Buchsbaum et a!., 1971; Cohn et al., i@@'o), has necessitated a revaluation of the question of outcome in this psychiatric illness. The ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(46 citation statements)
references
References 11 publications
4
41
0
1
Order By: Relevance
“…However, a substantial proportion of bipolar patients show persistent subsyndromal symptoms, and most individuals with bipolar disorder are symptomatic more than half of their lives despite receiving pharmacological treatment [3, 4]. Even those patients who achieve full clinical remission show difficulties in making a complete functional recovery, returning to their premorbid level of functioning [5,6,7,8,9,10,11,12,13,14,15,16,17,18]. Nevertheless, psychosocial outcomes in patients with bipolar disorder have generally received less attention than those in patients with psychosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, a substantial proportion of bipolar patients show persistent subsyndromal symptoms, and most individuals with bipolar disorder are symptomatic more than half of their lives despite receiving pharmacological treatment [3, 4]. Even those patients who achieve full clinical remission show difficulties in making a complete functional recovery, returning to their premorbid level of functioning [5,6,7,8,9,10,11,12,13,14,15,16,17,18]. Nevertheless, psychosocial outcomes in patients with bipolar disorder have generally received less attention than those in patients with psychosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, disability in occupational functioning is also a common consequence of bipolar disorder [40][41][42] . But previous works traditionally measured one or two elements of psychosocial functioning and there is not a consensual scale to assess its impact on bipolar patients.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of cognitive impairment has been held to be uncommon in bipolar disorder and much more likely in schizophrenia. Although several studies have reported a good outcome for bipolar patients, a subgroup of 5–34% have consistently been described as having poor social outcome or poor response to treatment [2, 3, 4, 5]. Furthermore, persistent cognitive deficits have been reported in up to 32% bipolar patients even in euthymic or asymptomatic states [6].…”
Section: Introductionmentioning
confidence: 99%